Pendidikan Matematika Realistik: Membangun Konsepsi Matematika dalam Budaya Sasak - Fauzi, Lalu Muhammad; Gazali, Muhammad; Fauzi, Asri; Wardi, Zaotul; Endriana, Neny (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2022)
In the context of cultural anthropology, people have known various mathematical activities, such as counting, measuring, and weighting, which have different terms based on each culture. We understand that mathematics emerges from people activities in responding to the existence of their environment. Sasak people conduct various cultural activities in their daily life. One of which is in agriculture and in the form of traditional arts, therefore, this study aims to build mathematical conceptions by exploring the activities of Sasak culture that can be integrated into mathematics learning contextually. This study was an ethnographic research. Data were collected through various literature studies, field observations, and interviews with savvy informants regarding Sasak culture, traditional farming system, and Sasak traditional arts. Research results indicated that the culture of Sasak people relevant with principles and characteristics of Realistic Mathematics Education (RME) is a learning approach that can be integrated, both explicitly and implicitly